Characterization of kappa-carageenan from the red alga Kappaphycus striatum - Hung, Le Dinh; Thi Huong, Dang (Vietnam Journal of Biotechnology, 2020)
The red alga Kappaphycus striatum is an economically important species and extensively cultivated in Vietnam as a material source for carrageenan production. To evaluate carrageenan quality, the characterization of carrageenan extracted from this alga was investigated. As a result, chemical composition of carrageenan consists of 32.4% of 3,6 anhydrogalactose and 24.3% of sulfate. Gelling and metling temperatures are 34.4oC and 55.6oC, respectively. Gel strength of 1.5% is 615 g/cm2 and average molecular weight is about 267 kDa. Furthermore, FT-IR spectrum showed intense absorption bands at 930 cm-1 and 850 cm-1 that attributed to 1,4-linked 3,6 anhydro-α-D-galactose and 1,3-linked β-D-galactose-4-sulfate of kappa-carrageenan, respectively. 13C NMR spectrum indicated the signals for anomeric carbon of β-D-galactose-4-sulfate at 102.6 ppm and anomeric carbon of 3,6-anhydro-α-D-galactose at 95.3 ppm. 13H NMR spectrum showed peak signals at 3.57 ppm and 5.1 ppm that corresponds with O-methyl proton of 1,3-linked 6-O-methyl-D-galactose and α-anomeric proton of 3,6 anhydro-α-D-galactose residues, respectively. The results show that the carrageenan from the red alga Kappaphycus striatus is kappa-carrageenan with the repeating disaccharide unit consisting of 1,3-linked 6-O-methylated, β-D-galactose-4-sulfate and 1,4-linked 3,6 anhydro-α-D-galactose and did not contain iota-carrageenan. Therefore, this alga may promise to be a good source for carrageenan production for application in food or medicine.